Community-based Disaster Preparedness; A Training Program Based on Needs Assessment - Mohammad H Yarmohammadian; Faezeh Akbari; Asal Sadat Niaraees Zavare; Fatemeh Rezaei (Health in Emergencies & Disasters Quarterly)
Background: This study aimed to develop an educational program to address the basic educational needs of community-based health organizations (CBHOs) or non-government organizations (NGOs) in Iran involved in disaster management. Materials and Methods: This qualitative study was conducted in two phases: a) Identifying the basic educational needs of CBHOs/NGOs before participating in disaster management through interviews with 25 key informants from Isfahan, Iran, and b) Validating the components by conducting focus group discussions with key informants and designing the educational program. Results: We extracted two main themes (goals): 1) Recognizing the conceptual foundations of CBHOs/NGOs with three categories (objectives) of “role and social status”, “structures”, and “practical approaches”, and 2) Attention to social determinants of health (SDH) with nine categories of “culture of safety”, “social responsibility”, “social cohesion”, “addiction prevention plans”, “women’s needs”, “mental health”, “ethical standards”, “ morale improvement”, and “communication skills”. The educational program was elaborated by specifying the syllabuses, educational strategies/teaching methods, target groups, duration, and budget for each objective. Conclusion: The educational program can be used to increase CBHOs/NGOs’ skills and knowledge, help them coordinate their actions, and adapt their responses to the diverse needs and preferences of the community.